2009
DOI: 10.1007/s11104-009-0175-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil carbon stock after deforestation and subsequent establishment of “Imperata” grassland in the Asian humid tropics

Abstract: Globally, tropical deforestation is often followed by the establishment of fire-prone grassland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…2). Possible explanations for the high total SOC s in grasslands, which were similar to SOC s in mature forest, are higher belowground net primary production (NPP) and charcoal inputs compared to forests (van der Kamp et al, 2009;Yonekura et al, 2010). Higher belowground NPP in Imperata grasslands compared to forests may result in greater inputs of organic matter to the soil.…”
Section: Effects Of Land-use Type On Soil Organic Carbon Concentratiomentioning
confidence: 98%
See 1 more Smart Citation
“…2). Possible explanations for the high total SOC s in grasslands, which were similar to SOC s in mature forest, are higher belowground net primary production (NPP) and charcoal inputs compared to forests (van der Kamp et al, 2009;Yonekura et al, 2010). Higher belowground NPP in Imperata grasslands compared to forests may result in greater inputs of organic matter to the soil.…”
Section: Effects Of Land-use Type On Soil Organic Carbon Concentratiomentioning
confidence: 98%
“…However, results from field measurements on impacts of fire and charcoal additions on SOC quantities are contradictory, ranging from SOC losses (Bird et al, 2000;Fynn et al, 2003) to no change or increases in the SOC pool (Eckmeier et al, 2007;Ojima et al, 1994). Studies conducted in Kalimantan, Indonesia (van der Kamp et al, 2009;Yonekura et al, 2010), reported even higher SOC s in Imperata grasslands compared to primary forests. Similarly, a meta-study of tropical landuse conversions (Powers et al, 2011) reported an increase in SOC s of 26 % following forest-to-grassland conversions on soils with low activity clays and annual precipitation of 1501-2500 mm, which are similar to the biophysical conditions in our study area.…”
Section: Effects Of Land-use Type On Soil Organic Carbon Concentratiomentioning
confidence: 99%
“…The estimated soil C stocks for the 0-to 30-cm depth range were 26.8 Mg C ha -1 in Southern Thailand 22 and 29.9 Mg C ha -1 in East Kalimantan 28 . Within the 0-to 100-cm depth range, estimates were 55.0 Mg C ha -1 in East Kalimantan 28 and 70.0 Mg C ha -1 in peninsular Malaysia 27 .…”
Section: Soil C Stock In Tropical Monsoon Forestsmentioning
confidence: 91%
“…The estimated soil C stocks for the 0-to 30-cm depth range were 26.8 Mg C ha -1 in Southern Thailand 22 and 29.9 Mg C ha -1 in East Kalimantan 28 . Within the 0-to 100-cm depth range, estimates were 55.0 Mg C ha -1 in East Kalimantan 28 and 70.0 Mg C ha -1 in peninsular Malaysia 27 . The studies mentioned above did not report C stocks in the 0-to 100-cm depth range of Andosols and Andisols 12,26 , although these are the largest stocks (>200 Mg C ha -1 ) in the humid tropics.…”
Section: Soil C Stock In Tropical Monsoon Forestsmentioning
confidence: 91%
See 1 more Smart Citation